Digital Governance and Smart Diplomacy: Transformation of State Administration on the International Stage - Ginanjar, Yusep (Universitas Sultan Ageng Tirtayasa, 2025)
The growth of technology for sharing information and communicating has led to major changes in how countries manage their affairs and conduct foreign relations. This study examines how online rule-making and smart diplomacy act as new ways to manage state affairs, changing with global trends. This study uses a simple descriptive method using book reviews and text examination techniques. Indonesia's shift to digital administration is a key strategy to create an effective and inclusive government system using technology and to enhance its global reputation with smart diplomatic methods. Digital rules create fast services using data studies and smart diplomacy, combining tradition with learning and protection to keep digital conversations safe for state purposes. Cities across the border are joining in as local cities become more involved and Indonesia grows its soft influence. Collaborative efforts lay the foundation for Indonesia to address global issues with flexible, environmentally friendly strategies that support Indonesia's digital plan for 2045.